2004
DOI: 10.1093/jxb/erh095
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a cDNA encoding asparaginyl endopeptidase from sweet potato (Ipomoea batatas (L.) Lam) senescent leaves

Abstract: Asparaginyl endopeptidase is a cysteine endopeptidase that has strict substrate specificity toward the carboxyl side of asparagine residues, and is possibly involved in the post-translational processing of proproteins. In this report one full-length cDNA, SPAE, was isolated from senescent leaves of sweet potato (Ipomoea batatas (L.) Lam). SPAE contained 1479 nucleotides (492 amino acids) in the open reading frame, and exhibited high amino acid sequence homologies (c. 61-68%) with asparaginyl endopeptidases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Asparaginyl endopeptidase is an atypical cysteine endopeptidase with a reported insensitivity to the inhibitor L-3-carboxy-2,3-trans-epoxypropionyl-leucylamino(4-guanidino)butane (E-64) (Okamoto & Minamikawa, 1999). A cysteine protease activity band with a molecular mass near 36 kDa similar to the protein gel blot results was also detected and exhibited insensitivity to E-64 inhibitor (Chen et al, 2004). These data provide indirect evidence to support the existence of asparaginyl endopeptidase in senescent leaves.…”
Section: Spaementioning
confidence: 68%
See 4 more Smart Citations
“…Asparaginyl endopeptidase is an atypical cysteine endopeptidase with a reported insensitivity to the inhibitor L-3-carboxy-2,3-trans-epoxypropionyl-leucylamino(4-guanidino)butane (E-64) (Okamoto & Minamikawa, 1999). A cysteine protease activity band with a molecular mass near 36 kDa similar to the protein gel blot results was also detected and exhibited insensitivity to E-64 inhibitor (Chen et al, 2004). These data provide indirect evidence to support the existence of asparaginyl endopeptidase in senescent leaves.…”
Section: Spaementioning
confidence: 68%
“…The conserved catalytic residues (His and Cys) and central -strands that supported the catalytic residues of human and mouse legumains (Chen et al, 1998) were also found in SPAE, plant legumain/asparaginyl endopeptidase, vacuolar processing enzymes, and the other cysteine proteases (Chen et al, 2004).…”
Section: Spaementioning
confidence: 82%
See 3 more Smart Citations